'Good administration' and the 'Good': The normative foundation for the protection of legitimate expectations. (December 2021) - Chng, Kenny
An idea that has gained significant traction in both case law and academic commentary as a justification for the protection of legitimate expectations is the concept of 'good administration'. Going beyond the usual criticisms of the concept's ambiguity, this article aims to highlight an additional set of difficulties with the invocation of 'good administration' as the normative justification for the doctrine. This article's central argument is that the concept of 'good' invoked by the idea of 'good administration' inevitably falls to be substantiated by a particular conception of what the 'good' requires as a matter of political philosophy. And given that there are multiple competing conceptions of what 'good' law and government are, this magnifies the challenges of coming to a landing on the precise content of 'good administration'. This article will illustrate that the various formulations of the normative foundation of the doctrine track closely with four different conceptions of 'good' law and government and will explore the implications of this diagnosis for the formulation of the proper justification for the protection of legitimate expectations.